A Case On Vodafone Group PLC: Sustaining Its Competitive Advantage In Global Market Expansion - Jaafar, Zarina (2005)
The analysis of this case study covers almost all aspects in the operations of Vodafone. Its starts with the introduction of the company itself and ends with the strategic plans of the company.